Gross Morphology and Morphometry of Bronchial Tree using Casting Method in Domestic Sheep (Ovis aries) - Vinayasheela, Santhapuri (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
The bronchial tree of sheep ( Ovis aries ) demonstrated species-specific anatomical features that reflect adaptation to ruminant physiology and grazing behaviour. The lung was composed of right and left lobes, with four and two sub-lobes each, respectively. The apical lobe and accessory lobes were present in the right lobe while cardiac and diaphragmatic lobes were seen in both right and left lobes. The cardiac notch was prominent in right lobe than in left lung cardiac lobe. A distinctive feature of the ovine bronchial tree was the presence of anapical bronchus supplying the right cranial lobe. The bronchial architecture exhibited both monopodial and dichotomous branching pattern, where the principal bronchus on right side showed four ventral, 5 dorsal and 3 lateral and 3 medial lobar (secondary) bronchi while that of left one emitted 5 dorsal, 6 lateral, 4 ventral, and 3 medial segmental bronchi but with a more consistent order of origin which thereafter continued as terminal segment. The morphometry revealed that the circumference of trachea before giving rise to apical bronchus was more (6.99 ± 0.93 cm) than after origin of apical bronchus (6.53 ± 1.12 cm), which increased at the level of bifurcation (7.10 ± 0.91 cm). The circumference of left principal bronchus (5.68 ± 0.70 cm) was higher and that of apical bronchus was least (3.03 ± 0.44 cm).